Optical design of a broadband spectrometer with compact structure based on echelle and concave gratings. (April 2022) - Fu, Xiao; Duan, Fajie; Jiang, Jiajia; Bao, Ruijia; Liu, Changwen; Li, Tianyu; Yu, Zhenxin
Highlights: A novel compact structure of a broadband (190–800 nm) spectrometer is proposed. An echelle and a concave grating is used to form cross-dispersive configuration. Broadband wavelength range and high resolution can be obtained. Abstract: In this work, we introduce a novel optical design of a broadband (190–800 nm) spectrometer with compact structure based on cross dispersed gratings. The design applies an off-axis parabolic mirror to collimate the light from the pinhole without inducing the astigmatism. Two crossed dispersive devices (an echelle grating and a concave grating) are utilized to produce a two-dimensional image, which contains information of the separated spectrum. The concave grating also works as the focusing element, which simplifies the system structure and improves the light throughput. The relationships between the imaging performance and the optical parameters are analyzed and according to this, we propose the detailed design method of this type of spectrometer, which may be suitable for other different conditions. The simulation result revealed that the spectral resolution of the spectrometer reaches 0.02nm(@190 nm), 0.05nm(@400 nm), 0.07nm(@600 nm) and 0.08nm(@800 nm).